ARTIFICIAL INTELLIGENCE - VARUN TYAGI, VARUN x; VERMA, SHUBAM; SINGH, PANKAJ (IJRDO -Journal of Computer Science Engineering, 2015)
The Connections Between Artificial Intelligence and Other Fields. Abstract Through examples from several fields, this paper will describe the connections between Artificial Intelligence and other areas. Some of these areas make great contributions to AI research, others gain knowledge and technique from that same AI research.This research paper gives us overview of artificial intelligence,history of artificial intelligence,goals of artificial intelligence,approaches and application of artificial intelligence